Heart of a samurai : based on the true story of Nakahama Manjiro - Preus, Margi (Amulet Books, 2012)
After fourteen-year-old Manjiro and his friends are stranded on an island in 1841, they are picked up by an American whaling ship where Manjiro becomes eager to learn about this new culture and describes his ten-year journey to places he'd never seen, including America. But Manjiro longs to return to his home in Japan and become a samurai. Includes biographical information about Manjiro, black-and-white illustrations, a glossary, and sources for additional information.